Simultaneous Burr Hole Drainage and Epidural Blood Patch with Real-Time ICP Monitoring for Subdural Hematoma Associated with Spontaneous Intracranial Hypotension: Case Report and Technical Note - Sunohara, Yuki; Nagashima, Yoshitaka; Nishimura, Yusuke; Choo, Jungsu; Sago, Fumihiro; Somiya, Daiki; Maeda, Kenko; Ikeda, Akira; Saito, Ryuta (Asian Journal of Neurosurgery, 2025)
Spontaneous intracranial hypotension (SIH) is a condition caused by cerebrospinal fluid (CSF) leakage, leading to low intracranial pressure (ICP), brain sagging, and subdural hematoma (SDH). Management of SIH complicated by SDH presents a clinical challenge: treating CSF leaks is performed by epidural blood patch (EBP), which elevates ICP, while SDH management typically requires hematoma evacuation, producing a reductive effect on ICP. Mismanagement can result in severe complications such as brain herniation or rebound intracranial hypertension. We report two cases of SIH-associated SDH successfully treated with simultaneous burr hole drainage and EBP, guided by continuous ICP monitoring. Both patients presented with significant SDHs and clinical signs of SIH. At the start of the procedure, subdural ICP was relatively low. After administration of autologous blood, ICP rose rapidly to over 30 mm Hg, reaching levels considered dangerously high if left unaddressed. The hematoma was evacuated without delay, and patients had no recurrence or complications. EBP under real-time monitoring facilitated timely intraoperative decisions and tailored responses to dynamic intracranial changes. This approach provides a framework for individualized and safe intervention in complex dual-pathology scenarios.
Keywords: cerebrospinal fluid leak; epidural blood patch; intracranial pressure monitoring; spontaneous intracranial hypotension; subdural hematoma